Electrocatalytic performance of copper selenide as structural phase dependent for hydrogen evolution reaction. (5th May 2023) - Iqbal, Muhammad Faisal; Jiang, Zhendong; Muhammad, Zahir; Hassan, Mahmood Ul; Li, Guijun; Zhao, Yuwei; Chen, Zhiying; Zhang, Meng
Abstract: A cost-effective, efficient and stable electrocatalyst is a remarkable and significant prospect for hydrogen evolution reaction. By adjusting the copper contents, the Hexagonal and Tetragonal phases of the copper selenide have been synthesized using the solvo-hydrothermal process. Hexagonal phased-based copper selenide has exhibited a greater current density than the Tetragonal phase. However, the augmented structure, lower Gibbs Free energy, greater electrical conductivity and electrochemical surface promoted the electrocatalytic behavior of Hexa-CuSe-1.04 nanosheets. Hexa-CuSe-1.04 nanosheets exhibit a good overpotential of 61 mV at the state of art current density of 10 mAcm −2 along with Tafel slope of 59 mV dec −1 in 1 M KOH, which is better than the other Hexagonal phase structure, Hexa-CuSe-1.67 nanosheets and Tetra-Cu2 Se-1.30 phase of the copper selenides. The electrocatalyst Hexa-CuSe-1.04 maintains the current density for a long duration and exhibits a similar linear sweep voltammetry curve in 1 M KOH during the chronoamperometry test. Moreover, Hexa-CuSe-1.04 nanosheets show a good Tafel slope of 26 mV dec −1 with a good turnover frequency of 72.40 m s −1 in 0.5 M H2 SO4 and follow the Tafel phenomenon. Optimized density functional theory reveals that Hexa-CuSe-1.04 exhibits the lower Gibbs of 1.04 eV, free energy, which promotes the desorption and recombination process of the active hydrogen atoms at the active sites and enhanced the hydrogen evolution process. All results indicate the leading potential application of the Hexagonal phase of Hexa-CuSe-1.04 for hydrogen evolution reaction. Graphical abstract: Image 1 Highlights: 1. Copper contents significantly influenced the growth process. 2. Intrinsic features depend significantly on the crystal structural phases. 3. Hexa-CuSe-1.04 exhibits greater electrical conductivity and low Gibbs Free energy. 4. Hexa-CuSe-1.04 exhibits a good overpotential of 61 mV in 1 M KOH. 5. Electrocatalyst, Hexa-CuSe-1.04 shows a Tafel slope of 26 mV dec −1 in M H2 SO4 .